The efficacy of sodium-glucose transporter 2 inhibitors in patients with nonalcoholic fatty liver disease: A systematic review and meta-analysis - Hongsheng Li; Yanli Hou; Wenyong Xin; Lina Ding; Ying Yang; Yikun Zhang; Wenqi Wu; Zhibin Wang; Wenyu Ding (Pharmacological Research)
The efficacy of sodium-glucose transporter 2 (SGLT-2) inhibitors for nonalcoholic fatty liver disease (NAFLD) is unclear. Therefore, we conducted a systematic review and meta-analysis to evaluate SGLT-2 inhibitors efficacy for NAFLD treatment. We systematically searched major electronic databases (PubMed, Cochrane Library, Web of Science, Embase) from inception until 11/2023, identifying randomized controlled trials (RCTs) of SGLT-2 inhibitors treatment for patients with NAFLD. The mean differences (MD or SMD) and 95 % confidence intervals (CIs) were calculated via random-effects models. Eleven articles (n = 805 patients with NAFLD) were included in this study. Of these, 408 participants received SGLT-2 inhibitors, while 397 participants were in the control group. SGLT-2 inhibitors significantly reduced liver enzyme levels, including aspartate alanine aminotransferase (ALT) (MD [95 % CI]; −9.31 U/L [-13.41, −5.21], p < 0.00001), aspartate aminotransferase (AST) (MD [95 % CI]; −6.06 U/L [-10.98, −1.15], p = 0.02), and gamma-glutamyltransferase (GGT) (MD [95 % CI]; −11.72 U/L [-15.65, −7.80], p < 0.00001). SGLT-2 inhibitors intervention was also associated with significant reductions in body weight (MD [95 % CI]; −2.72 kg [-3.49, −1.95], p < 0.00001) and BMI (MD [95 % CI]; −1.11 kg/m2 [-1.39, −0.82], p < 0.00001) and improvements in glycaemic indices, triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C). However, no significant changes in total cholesterol (TC) or low-density lipoprotein cholesterol (LDL-C) were observed. The meta-analysis revealed a beneficial effect of SGLT-2 inhibitors on liver functions and body weight, BMI, TG, HDL-C, and glucose homeostasis in patients with NAFLD, indicating that SGLT-2 inhibitors might be a clinical therapeutic strategy for these patients, especially individuals with concurrent type 2 diabetes mellitus (T2DM).